Oceans : dolphins, sharks, penguins, and more! : meet 60 cool sea creatures and explore their amazing watery world - Rizzo, Johnna (Washington, D.C. : National Geographic, 2010)
Photographs and fun facts explore the lives and homes of a variety of sea creatures, including sharks, dolphins, sea turtles, penquins, and many others.
"National Geographic Kids."
Includes index.
6.7
3-6
3-6
1190L
Keywords: Ocean -- Juvenile literature; Marine biology -- Juvenile literature; Ocean; Marine biology; Ocean; Marine biology